2004
DOI: 10.1002/dys.281
|View full text |Cite
|
Sign up to set email alerts
|

Time reproduction in finger tapping tasks by children with attention‐deficit hyperactivity disorder and/or dyslexia

Abstract: The results indicate that motor timing ability in the millisecond range below 1000 ms in children with ADHD and/or dyslexia is intact. The performance of the comorbid group was revealed to be similar to the performance of the single disorder groups, but both the dyslexic groups were relatively worse than either the ADHD-only or the unimpaired group at reproducing complex versus simple rhythms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 27 publications
2
29
0
3
Order By: Relevance
“…However, such anecdotes appear to refer to very different time frames and contexts to this under consideration herein. Temporal information processing has been reported to be impaired in studies of ADHD samples (for example, Barkley et al, 1997Barkley et al, , 2001aBarkley, 1997aBarkley, , 1998Bauermeister et al, 2005;Breier et al, 2003;Kerns et al, 2001;McGee et al, 2004;Mullins et al, 2005;Radonovich and Mostofsky, 2004;Rubia et al, 2003;Smith et al, 2002;Sonuga-Barke et al, 1998;Tiffin-Richards et al, 2004;Toplak and Tannock, 2005a,b;Toplak et al, 2003;Van Meel et al, 2005;West et al, 2000), although findings are not always consistent (see Table 1). Most of these studies have been conducted in child samples, but some report data in adolescents (Barkley et al, 2001a,b;Rubia et al, 1999a;Toplak and Tannock, 2005a,b;Toplak et al, 2003) and some in adults (Barkley et al, 2001b;Seri et al, 2001).…”
Section: Empirical Evidence Of Temporal Information Processing Deficimentioning
confidence: 99%
See 1 more Smart Citation
“…However, such anecdotes appear to refer to very different time frames and contexts to this under consideration herein. Temporal information processing has been reported to be impaired in studies of ADHD samples (for example, Barkley et al, 1997Barkley et al, , 2001aBarkley, 1997aBarkley, , 1998Bauermeister et al, 2005;Breier et al, 2003;Kerns et al, 2001;McGee et al, 2004;Mullins et al, 2005;Radonovich and Mostofsky, 2004;Rubia et al, 2003;Smith et al, 2002;Sonuga-Barke et al, 1998;Tiffin-Richards et al, 2004;Toplak and Tannock, 2005a,b;Toplak et al, 2003;Van Meel et al, 2005;West et al, 2000), although findings are not always consistent (see Table 1). Most of these studies have been conducted in child samples, but some report data in adolescents (Barkley et al, 2001a,b;Rubia et al, 1999a;Toplak and Tannock, 2005a,b;Toplak et al, 2003) and some in adults (Barkley et al, 2001b;Seri et al, 2001).…”
Section: Empirical Evidence Of Temporal Information Processing Deficimentioning
confidence: 99%
“…When stimulus rate was altered within the same tapping task, Ben-Pazi et al (2003) found that children with ADHD had difficulty modifying their tapping rate to be in synchrony with the stimulus. Then, one study reported no significant group differences between ADHD and control groups on a complex rhythm tapping task (Tiffin-Richards et al, 2004). Given the differences in the types of methods that have been used, it is impossible to draw conclusions about tapping performance in ADHD samples.…”
Section: Empirical Evidence Of Temporal Information Processing Deficimentioning
confidence: 99%
“…The role of comorbid RD in studies with ADHD that examine time perception deficits is, however, unclear. Tiffin-Richards et al (2004) studied time reproduction in finger-tapping tasks in children with ADHD, children with RD, children with both ADHD and RD, and non-diagnosed controls. The clinical groups did not differ from controls on the time reproduction tasks.…”
Section: Endophenotypes Of Comorbidity Of Adhd and Rd 183mentioning
confidence: 99%
“…The time perception of auditory stimuli was evaluated using discrimination tasks (which involve only time perception) and reproduction tasks (which also require motor responses). Tiffin-Richards et al (2004) did not find differences among the groups (ADHD, RD, ADHD+RD and control) on any task, which would indicate that the capacity to maintain a certain response rate (free-tapping) or adjust the response to a certain stimulus pattern (synchronized tapping) was not affected in any of the clinical groups. Furthermore, the groups analyzed did not show differences in intra-individual variability when reproducing different intervals.…”
Section: Adhd and Rd Single Dissociation Studiesmentioning
confidence: 74%
“…Somewhat different results on time perception were obtained by Tiffin-Richards, Hasselhorn, Richards, Banaschewsky and Rothenberger (2004), who examined the performance of German children using a computer-mediated finger-tapping paradigm. The time perception of auditory stimuli was evaluated using discrimination tasks (which involve only time perception) and reproduction tasks (which also require motor responses).…”
Section: Adhd and Rd Single Dissociation Studiesmentioning
confidence: 94%